PENERAPAN MODEL PROBLEM BASED LEARNING UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPS DI KELAS IV SD INPRES BERU TAHUN AJARAN 2023/2024 - Dua Kowe, Genoveva Lise; Florida Yandalima, Maria; Yufrinalis, Marianus (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine how the use of the Problem-Based Learning (PBL) model can improve student learning outcomes in Social Studies (IPS) learning and to assess student learning outcomes when using the PBL model. This research is a classroom action research (CAR), which is a practical study intended to improve learning in the classroom. The subjects of this study were 20 fourth-grade students of SD Inpres Beru. The research data were collected using field notes, interviews, and documentation techniques. Based on the research design used, data analysis was conducted through analysis and reflection in each cycle, based on observations recorded in field notes and other observation formats. The teacher carried out learning activities according to the indicators and learning objectives, and students actively presented the results of their discussions in front of the class. Through the application of the Problem-Based Learning model in Social Studies learning on the topic of